2014
DOI: 10.1002/2014gl061232
|View full text |Cite
|
Sign up to set email alerts
|

Paleotsunami evidence on Kaua‘i and numerical modeling of a great Aleutian tsunami

Abstract: The Hawaiian Islands' location in the middle of the Pacific Ocean is threatened by tsunamis from great earthquakes in nearly all directions. Historical great earthquakes Mw > 8.5 in the last 100 years have produced large inundations and loss of life in the islands but cannot account for a substantial (≤ 600 m3) paleotsunami deposit in the Makauwahi sinkhole on the Island of Kaua‘i. Using high‐resolution bathymetry and topography we model tsunami inundation of the sinkhole caused by an earthquake with a moment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 14 publications
1
40
0
Order By: Relevance
“…1A;Nishenko and Jacob, 1990;Vallier et al, 1994;Carver and Plafker, 2008;Ryan et al, 2012b;Ruppert et al, 2013;Butler et al, 2014;Shennan et al, 2014b). That the Aleutian arc is capable of sending damaging tsunamis across the Pacific basin is illustrated by those produced by the series of mid-twentieth century M 8-9 ruptures in the central and eastern Aleutian arc, in 1946, 1957, 1964, and 1965(Butler, 2012Ross et …”
Section: Introductionmentioning
confidence: 99%
“…1A;Nishenko and Jacob, 1990;Vallier et al, 1994;Carver and Plafker, 2008;Ryan et al, 2012b;Ruppert et al, 2013;Butler et al, 2014;Shennan et al, 2014b). That the Aleutian arc is capable of sending damaging tsunamis across the Pacific basin is illustrated by those produced by the series of mid-twentieth century M 8-9 ruptures in the central and eastern Aleutian arc, in 1946, 1957, 1964, and 1965(Butler, 2012Ross et …”
Section: Introductionmentioning
confidence: 99%
“…In parallel with this study, Butler et al (2014) analyzed and dated the paleotsunami site in the Makauwahi sinkhole on the southeastern coast of Kaua'i between Po'ipu and Nawiliwili harbor (orange star in Fig. 3), positing evidence for a great tsunami there in the sixteenth century.…”
Section: Tsunami Inundations For the Earthquake Scenariosmentioning
confidence: 94%
“…Results indicate that an Eastern Aleutian earthquake of Mw 9.25 or greater is necessary to inundate the site. See Butler et al (2014) for details and further discussion.…”
Section: Tsunami Inundations For the Earthquake Scenariosmentioning
confidence: 99%
“…Butler et al . () inferred that a tsunami had overtopped the sinkhole wall at its lowest point (7·2 m above sea level). Numerical tsunami modelling by these authors demonstrated that a Mw ca 9·25 earthquake centred in the eastern Aleutians would have been required to generate a tsunami large enough to overtop the sinkhole rim and create the deposit.…”
Section: Sedimentary Evidence Of Historical and Prehistoric Distant‐smentioning
confidence: 97%
“…However, a M w 9·25 or larger eastern Aleutian earthquake, as proposed by Butler et al . (), would presumably result in much larger runups that would be capable of inundating far into the valley interior.…”
Section: Study Areamentioning
confidence: 97%